PROMINENT LABOUR DIALECTOLOGY - Vasylevych, G. Y. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Review of book of Nick Lesiuk „Linguistic world of modern galitscogo village (Covalivca Colomiysk district"). – Ivano-Francovsk: New Sunset, 2008. – 328 s.